Peningkatan Pemahaman Konsep Bilangan Melalui Permainan Memancing Angka Pada Anak Usia 4-5 Tahun Di TK Pertiwi XI Merauke - Rani Nur Lidiawati; Hariani Fitrianti; Diah Harmawati; Retno Wuri Sulistyowati (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to improve understanding of the concept of numbers using number fishing media in children aged 4-5 years at Kindergarten Pertiwi XI Merauke for the 2022/2023 academic year. This research is classroom action research and was carried out over 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The subjects of this research were 8 children from group A of Kindergarten Pertiwi XI Merauke for the 2022/2023 academic year, consisting of 4 boys and 4 girls. Data collection techniques use observation and documentation. The instruments used are observation sheets for the ability to recognize number concepts and observation sheets for student and teacher activities. Data analysis uses descriptive statistical data analysis. The research results show that the use of number fishing media can improve children's ability to recognize number concepts. This can be shown from the learning success in the category of minimally developing according to expectations or three stars increasing from 12.5% ​​in the pre-cycle to 12.5% ​​in cycle I and 87.5% in cycle II. Apart from that, there was also an increase in student activity in the very active category of 25% in cycle I, an increase of 75% in cycle II and teacher activity in the learning process increased in both categories in cycle I and cycle II by 100%. So it can be concluded that the use of number fishing media can increase understanding of the concept of numbers in young children 4-5 years old at Kindergarten Pertiwi XI Merauke.